Merging Indigenous and Modern Knowledge in Agricultural Development - Nurdiah Husnah; M. Saleh S. Ali; Darmawan Salman; Pawennari Hijjang; Fadjry Djufry; A. Amidah Amrawaty (International Journal of Agriculture System, 2015)
This paper highlights the importance of merging indigenous with modern knowledge in agricultural development. Development of indigenous knowledge within the farming community, as a primary livelihood is now quite urgent. Development of technological-based local knowledge by the general public farmers seemed to be much easier for adoption because the technology actually originated from the local community, customs and local culture. Several studies have emphasized the importance of merging together the available indigenous and modern knowledge. It can be concluded that the rapid development of agriculture in remote rural areas in South Sulawesi, Indonesia requires significant merger of both the indigenous knowledge and modern agricultural systems. However, in order to ensure that the farmers can produce suitable and more effective modern adopted technologies, it has to be based on local wisdom. This adoption of modern technological knowledge ranges from the acquisition, dissemination and utilization of such beneficial knowledge in the Indonesian agricultural system. It is expected that such hybrids of local knowledge and modern technological know-how will help to create a mutual cooperation and knowledge contribution that encourages the development of strategic innovations and appropriate policies in the current local agricultural systems.